IMPLEMENTASI PERATURAN DAERAH NOMOR 1 TAHUN 2023 TENTANG PERLINDUNGAN LAHAN PERTANIAN PANGAN BERKELANJUTAN DI KABUPATEN TABALONG - Norliana Norliana; Ergina Faralita (PEPAKEM: JURNAL HUKUM TATA NEGARA DAN POLITIK ISLAM, 2025)
Agricultural land conversion resulting from infrastructure development and increasing spatial demands potentially threatens the sustainability of food production in Tabalong Regency, one of the supporting regions of Indonesia’s new capital, Nusantara. This study aims to analyze the implementation of Tabalong Regency Regional Regulation Number 1 of 2023 concerning the Protection of Sustainable Food Agricultural Land and the factors influencing its implementation. This study employed a qualitative method with an empirical legal or socio-legal approach. Informants were purposively selected from regional government agencies responsible for agriculture and spatial planning and from farmers cultivating land within designated sustainable agricultural areas. Data were collected through in-depth interviews, field observations, and document analysis and were examined using George C. Edward III’s policy implementation framework, comprising communication, resources, disposition, and bureaucratic structure. The findings demonstrate that the regulation has been implemented through the designation of sustainable food agricultural areas, the provision of agricultural production assistance, and supervision of land use. Nevertheless, its implementation remains suboptimal because policy dissemination is uneven, public understanding is limited, irrigation infrastructure and agricultural incentives are inadequate, land data are not fully integrated, supervision is inconsistent, and implementing regulations have not yet been issued. This study confirms that effective agricultural land protection cannot rely solely on land designation and conversion prohibitions but requires technical regulations, cross-sectoral coordination, economic support for farmers, integrated information systems, and participatory supervision.